Microscopic polyangiitis initially presenting with idiopathic pulmonary fibrosis: a case report - Shao, Chi; Chen, Ruxuan; Huang, Hui; Zhao, Yang; Chen, Keqi; Xu, Kai (Frontiers in Medicine, 2023)
Usual interstitial pneumonia is the most common type of microscopic polyangiitis (MPA)-associated interstitial lung disease, and patients may initially present with isolated pulmonary fibrosis, which often leads to a misdiagnosis of idiopathic pulmonary fibrosis (IPF). Here, we describe a patient who developed fever of unknown origin, microscopic hematuria and renal insufficiency, who then tested positive for antineutrophil cytoplasmic antibody (ANCA) and was diagnosed with MPA after receiving antifibrotic medication for IPF (original diagnosis) for almost 10 years. The patient’s symptoms were ameliorated after administration of additional glucocorticoids and immunosuppressants.